Student Alignments Toward the Values of Economic Culture. Issue 2 (3rd March 2016) - Mogil'chak, E.L.
Abstract : Research on the connection between Russian students' personal and occupational values shows success is defined in terms of personal wealth and power and labor values of responsibility, self-sufficiency, and creativity in the workplace.